2015
DOI: 10.1039/c5ra09960a
|View full text |Cite
|
Sign up to set email alerts
|

Carbastannatranes: a powerful coupling mediators in Stille coupling

Abstract: Stille coupling is an emerging application of carbastannatranes in organic synthesis because of their excellent tendency to transfer the axial Sn-bound hydrocarbyl substituent. Carbastannatranes have become powerful and versatile cross-coupling mediators in conventionally difficult synthetic routes for producing numerous organic compounds. These reagents belong to the most interesting class of tricyclic compounds, i.e. atranes, which captured the attention of researchers due to the uniqueness of the transannul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 92 publications
(175 reference statements)
0
6
0
Order By: Relevance
“…That was the first example of cine-substitution for imidazo [1,2-a]pyridines. Earlier in this review 9,29,33 it was described that the 3-nitrogroup in trinitroquinolone 67 treated with some carbon nucleophiles such as carbanions from 1,3-dicarbonyls, methyl ketones or neutral enamines could undergo cine-substitution with C-C-bond formation at the position 4. Later, Nishiwaki et al 40 showed that treatment of compound 67 with an excess of aliphatic primary amines could be an effective approach for the formation of the C (4) Unfortunately, cine-substitution of quinolone 67 to afford products 91 was possible only for sterically unhindered amines such as propylamine or isobutylamine.…”
Section: Page 418mentioning
confidence: 99%
See 1 more Smart Citation
“…That was the first example of cine-substitution for imidazo [1,2-a]pyridines. Earlier in this review 9,29,33 it was described that the 3-nitrogroup in trinitroquinolone 67 treated with some carbon nucleophiles such as carbanions from 1,3-dicarbonyls, methyl ketones or neutral enamines could undergo cine-substitution with C-C-bond formation at the position 4. Later, Nishiwaki et al 40 showed that treatment of compound 67 with an excess of aliphatic primary amines could be an effective approach for the formation of the C (4) Unfortunately, cine-substitution of quinolone 67 to afford products 91 was possible only for sterically unhindered amines such as propylamine or isobutylamine.…”
Section: Page 418mentioning
confidence: 99%
“…In their microreview, Peng and Li 8 focused on the cine-substitution in Stille cross-coupling reactions which often occurred with sterically hindered vinyltin components (over 50 references). Much later Kaur et al in a review 9 on carbastannatranes as mediators in Stille coupling also gave an example of cine-substitution. Ni-catalyzed Suzuki-Miyaura, Fe-catalyzed Kumada cross-coupling reactions of phenol-based electrophiles and other reactions of unconventional phenol derivatives including cine-substituted products were reviewed by Mesganaw and Garg (5 references).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, "atrane-like" cages are comprised of two bridgehead atoms (M and N) connected by identical or different podand arms containing 3 and/or 4 atoms. [18][19][20][21][22] The additional N-M bond provides better chelation to stabilize the transition-metal coordination sphere [17,[23][24][25][26][27][28][29][30][31][32][33][34] and/or main-group metal compounds. [35][36][37] In the past, several main-group compounds and transition-metal complexes containing "atrane-like" structures with unsymmetrical podands and their derivatives have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In line with our interest in glycoconjugate synthesis via cross-coupling with anomeric nucleophiles, [64][65][66][67][68] we hypothesized that a stable stannane could be installed at the β carbon in alanine. Tetraalkylstannanes are generally considered poorly nucleophilic, but selective transfer of alkyl groups can be achieved using carbastannatranes [69][70][71][72][73] leading us to propose amino acids with the general formula Ala Sn 11 as competent reagents for umpolung functionalization. Carbastannatranes are significantly less toxic than "normal" stannanes 74 and are compatible with aqueous and buffered conditions.…”
Section: Introductionmentioning
confidence: 99%